Design of hybrid split-capacitors and split-inductors applied in positive output super-lift luo-converters - Huang, Song. (2011)
The DC/DC conversion technology has been developed very fast over the decades, and many new types of DC/DC converters are designed. As a very important part of the DC/DC conversion technology, voltage-lift (VL) technology has been widely used in design of DC/DC converters, and the theory is maturely built. While the output voltage of this kind of converters only increases in arithmetic progression when more stages are added. By using super-lift (SL) technique, the output voltage will increase in geometric progression. In this paper, a novel approach is introduced – super-lift Luo-converters armed with split-capacitors and split-inductors. By replacing the original capacitors and inductors with these split elements the output voltage will be lifted to another higher level. This is a very important contribution to the conversion technology by Professor Luo Fang Lin. In this report, formulas and simulation results are presented and analyzed.